Design, operation and evaluation of mobile communications : first International Conference, MOBILE 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings /: first International Conference, MOBILE 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. (2020) - Unknown
No abstract available